Genome sequencing and flavor compound biosynthesis pathway analyses of Bacillus licheniformis isolated from Chinese Maotai-flavor liquor-brewing microbiome. Issue 3 (2nd July 2020) - Yang, Fan; Liu, Yanfeng; Chen, Liangqiang; Li, Jianghua; Wang, Li; Du, Guocheng
ABSTRACT: Maotai-: flavor liquor is one of the most popular distilled liquors in China that contains various flavor substances produced by a specialized brewing microbiome. Bacillus licheniformis is one of the major bacterial species in the Maotai -flavor liquor-brewing microbiome. However, the whole genome sequence of the B. licheniformis brewing strain has not been reported, which hampers further understanding of its effects on brewing. In this study, whole genome sequencing of B. licheniformis MT-B06 isolated from Maotai Daqu, a fermented wheat starter containing brewing microorganisms, was carried out using the Pacific Bioscience RS II platform. The sequence had a length of 4, 440, 765 bp with 45.7% GC content, encoding 5023 CDS sequences, 81 tRNAs, and 24 rRNAs. Next, genome annotation was performed based on four high-quality databases, including the COG, KEGG, GO/IPR, and Swiss-Prot databases. The genome sequence obtained was comparatively analyzed with that of B. licheniformis ATCC 14580, which is used for industrial enzyme production, which revealed that 69.95% of the differential genes are metabolically related, suggesting that these genes may be closely related to the flavor compounds biosynthesis. Therefore, the flavor compounds biosynthesis pathways and 26 relevant genes of B. licheniformis MT-B06 was analyzed, including alsS and alsD for 3-hydroxy-2-butanone synthesis, ispD, and ispE for terpenoids synthesis. This is the first report of high-quality whole genome sequencing of B. licheniformis MT-B06. Our results provide an important foundation for investigating metabolic pathways of desired compounds, such as C4 compounds and pyrazines, in Maotai- flavor liquor to improve its taste and quality.